Avaliação da produção biotecnológica de 2-feniletanol em resíduo líquido de fecularia - Oliveira, Simone Maria Menegatti de (2010)
2-phenylethanol is the most used fragrance in the food, cosmetics and fragrance industry. It is mainly produced by chemical process, but with many impurities. The biotechnological process of production is feasible and is being studied with various microrganisms, among them, Geotrichum fragrans, Saccharomyces cerevisiae and Kluyveromyces marxianus. The use of cassava wastewater as substrate in this process makes it less expensive and reduce environmental pollution caused by it. The objective or this work was to evaluate the production of 2-phenylethanol in the cultivation of Geotrichum fragrans, Saccharomyces cerevisiae and Kluyveromyces marxianus in cassava wastewater, analyzing the effect of two carbon sources on production of the aroma, besides increasing the production of 2 - phenylethanol to the greater efficiency of conversion carbon source/2-feniletanol, varying concentrations of carbon source and phenylalanine at cassava wastewater. For this, the three microrganisms mentioned were cultured in 50mL cassava wastewater plus 50g.L-1 of glucose and 3g.L-1 of L-phenylalanine in sterile Erlenmeyer flasks, on shaker at 150 rpm, 24 ° C for 120 hours, to check the time of peak production of 2-phenylethanol and what microrganism largest producer. It was then checked the production of aroma with 50g.L-1 of glucose and fructose, while maintaining the same amount of L-phenylalanine. And finally, by fatorial design, were tested concentrations of glucose and L-phenylalanine, in order to obtain higher yield and bioconversion of 2-phenylethanol. The experimental model was validated. It was analyzed in the pH, COD, reducing sugars, L-phenylalanine and 2-phenylethanol. In the precipitate was quantified indirectly as biomass, the Volatile Suspended Solids. The results showed that S. cerevisiae was the best producer of 2-phenylethanol in the effluent of cassava starch, obtaining 0.74 g.L-1, followed by K. marxianus, with 0.19 g.L-1 and finally by G. fragrans with 0.08 g.L-1. Glucose was the best carbon source for obtention of 2- phenylethanol for S. cerevisiae and K. marxianus. There was no significant difference between the production of 2-phenylethanol using glucose or fructose for G. fragrans. The best combination of glucose and L-phenylalanine for production of 2-phenylethanol, was 20,0 and 5.5 g.L-1 respectively, obtaining production of 1.33 g.L-1of aroma in the validation.